2016
DOI: 10.1007/s12020-016-1186-0
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan fasting in patients with adrenal insufficiency

Abstract: In patients with adrenal insufficiency, fasting can cause complications especially if the level of knowledge about the disease is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…AI patients should be instructed to hydrate well during non-fasting periods, maintain normal salt intake, and avoid strenuous activities during fasting. The pre-dawn meal, or Suhor, should be rich in complex carbohydrates, healthy proteins, and fats, and should be delayed to right before fasting starts (25). Additionally, all patients should be instructed to carry a steroid emergency card and a medical alert bracelet at all times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AI patients should be instructed to hydrate well during non-fasting periods, maintain normal salt intake, and avoid strenuous activities during fasting. The pre-dawn meal, or Suhor, should be rich in complex carbohydrates, healthy proteins, and fats, and should be delayed to right before fasting starts (25). Additionally, all patients should be instructed to carry a steroid emergency card and a medical alert bracelet at all times.…”
Section: Discussionmentioning
confidence: 99%
“…AI patients should always be supplied with i.m. glucocorticoid preparations for self-injection in the event of severe illness, trauma, or persistent vomiting, and advised to go to the hospital after the emergency injection ( 25 ). In our study, only half reported providing patients with specific recommendations regarding breaking their fast and/or seeking help when hypoadrenal symptoms occur, the latter of which may subject AI patients to unforeseen risks and preventable dangers.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] In Islamic culture, patients with adrenal insufficiency can suffer from hypoglycemia during Ramadan fasting, despite the continuance of glucocorticoid replacement therapy. 15 These reports indicate adrenalinsufficient adults are also prone to hypoglycemia, especially during fasting, and that the frequency may have been underestimated. For an early diagnosis, adrenal insufficiency must be considered if hypoglycemia due to an uncertain etiology is observed.…”
Section: Discussionmentioning
confidence: 99%
“…The risks of fasting were evaluated in 180 hypoadrenal patients. [40] Of these, 138 were advised by their physicians not to fast and but 91 patients (50.5%) tried to fast. Complications occurred in two-thirds of the patients including asthenia, symptoms of dehydration, intense thirst, and symptoms of hypoglycemia in decreasing frequencies.…”
Section: Endocrine and Metabolic Disordersmentioning
confidence: 99%